The Efficiency of Islamic Banks in the Middle East and Southeast Asia: Stochastic Frontier Approach - Adawiyah, Robi'atul; Suhel, Suhel; Syathiri, Ahmad (Equilibrium: Jurnal Ekonomi Syariah, 2023)
This research aims to compare and analyze the efficiency of Islamic banking in Southeast Asia and the Middle East by examining particular inputs such as third-party funds, operational expenses, labor costs, and return on assets, focusing on financing as the output. This quantitative study uses a purposive sampling technique to sample 30 sharia banks from Southeast Asia and 30 sharia banks from the Middle East from 2015 to 2022. The data used is secondary data from BankFocus and the annual financial reports of each bank. Data was processed using the Frontier 4.1 application with the Stochastic Frontier Analysis method. The results of this research show that the efficiency of sharia banking in the Middle East is higher than sharia banking in Southeast Asia. On the other hand, the return on assets has no impact on financing, but the input of third-party funds, operational expenses, and labor costs all have an impact. These findings show the importance of efficiently supervising the management of third-party funds and costs incurred by banks in order to improve banking performance. Hence, this will ultimately lead to an increase in the efficiency of sharia banking and a growth of banking profits.